KINSHIP AS A POLITICAL ACT: Responding to Political Exclusion through Communities of Solidaristic Kinship - Calleja, Carlo (Asian Horizons, 2020)
University/Institution: Boston College, USA Faculty/Department: Theology Director of the Doctoral Dissertation: Andrea Vicini, SJ, MD, PhD, STD Year of Doctoral Defence: 2020